Effect of Increased Lactate Dehydrogenase A Activity and Aerobic Glycolysis on the Proinflammatory Profile of Autoimmune CD8+ T Cells in Rheumatoid Arthritis. Issue 12 (8th November 2020) - Souto‐Carneiro, M. Margarida; Klika, Karel D.; Abreu, Mónica T.; Meyer, André P.; Saffrich, Rainer; Sandhoff, Roger; Jennemann, Richard; Kraus, Franziska V.; Tykocinski, Lars; Eckstein, Volker; Carvalho, Lina; Kriegsmann, Mark; et al.
Abstract : Objective: CD8+ T cells contribute to rheumatoid arthritis (RA) by releasing proinflammatory and cytolytic mediators, even in a challenging hypoxic and nutrient‐poor microenvironment such as the synovial membrane. This study was undertaken to explore the mechanisms through which CD8+ T cells meet their metabolic demands in the blood and synovial membrane of patients with RA. Methods: Purified blood CD8+ T cells from patients with RA, patients with psoriatic arthritis (PsA), and patients with spondyloarthritis (SpA), as well as healthy control subjects, and CD8+ T cells from RA synovial membrane were stimulated in medium containing 13 C‐labeled metabolic substrates in the presence or absence of metabolic inhibitors, under conditions of normoxia or hypoxia. The production of metabolic intermediates was quantified by 1 H‐nuclear magnetic resonance. The expression of metabolic enzymes, transcription factors, and immune effector molecules was assessed at both the messenger RNA (mRNA) and protein levels. CD8+ T cell functional studies were performed. Results: RA blood CD8+ T cells met their metabolic demands through aerobic glycolysis, production of uniformly 13 C‐enriched lactate in the RA blood (2.6 to 3.7–fold higher than in patients with SpA, patients with PsA, and healthy controls; P < 0.01), and induction of glutaminolysis. Overexpression of Warburg effect–linked enzymes in all RA CD8+ T cell subsets maintained this metabolic profile, conferring to the cells the capacity to proliferate under hypoxia and low‐glucose conditions. In all RA CD8+ T cell subsets, lactate dehydrogenase A (LDHA) was overexpressed at the mRNA level ( P < 0.03 versus controls; n = 6 per group) and protein level ( P < 0.05 versus controls; n = 17 RA patients, n = 9 controls). In RA blood, inhibition of LDHA with FX11 led to reductions in lipogenesis, migration and proliferation of CD8+ T cells, and CD8+ T cell effector functions, while production of reactive oxygen species was increased by 1.5‐fold ( P < 0.03 versus controls). Following inhibition of LDHA with FX11, RA CD8+ T cells lost their capacity to induce healthy B cells to develop a proinflammatory phenotype. Similar metabolic alterations were observed in RA CD8+ T cells from the synovial membrane. Conclusion: Remodeling glucose and glutamine metabolism in RA CD8+ T cells by targeting LDHA activity can reduce the deleterious inflammatory and cytolytic contributions of these cells to the development of autoimmunity.